Understanding role of pesticides in development of Parkinson's disease: Insights from Drosophila and rodent models. - Afsheen, S.; Rehman, A.S.; Jamal, A.; Khan, N.; Parvez, S. (Ageing Research Reviews, 2024)
Parkinson's disease is a neurodegenerative illness linked to ageing, marked by the gradual decline of dopaminergic neurons in the midbrain. The exact aetiology of Parkinson's disease (PD) remains uncertain, with genetic predisposition and environmental variables playing significant roles in the disease's frequency. Epidemiological data indicates a possible connection between pesticide exposure and brain degeneration. Specific pesticides have been associated with important characteristics of Parkinson's disease, such as mitochondrial dysfunction, oxidative stress, and ?-synuclein aggregation, which are crucial for the advancement of the disease. Recently, many animal models have been developed for Parkinson's disease study. Although these models do not perfectly replicate the disease's pathology, they provide valuable insights that improve our understanding of the condition and the limitations of current treatment methods. Drosophila, in particular, has been useful in studying Parkinson's disease induced by toxins or genetic factors. The review thoroughly analyses many animal models utilised in Parkinson's research, with an emphasis on issues including pesticides, genetic and epigenetic changes, proteasome failure, oxidative damage, ?-synuclein inoculation, and mitochondrial dysfunction. The text highlights the important impact of pesticides on the onset of Parkinson's disease (PD) and stresses the need for more research on genetic and mechanistic alterations linked to the condition.